Late Gadolinium Enhancement in the Left Ventricular Wall Is Associated with Atrial Fibrillation in Patients with Hypertrophic Cardiomyopathy - Castelo, A (2022)
Purpose: Atrial fibrillation (AF) is the most common arrhythmia in patients with hypertrophic cardiomyopathy (HCM). The aim of this study was to evaluate the relation between AF and left ventricular (LV) late gadolinium enhancement (LGE). Methods: 55 patients with HCM were retrospectively included. Patients were divided in HCM with AF and HCM without AF. Baseline clinical, echocardiographic and cardiovascular magnetic resonance (CMR) characteristics were collected and compared between groups. Results: In univariable analysis, the factors related to AF development were HCM risk score for sudden cardiac death (SCD) > 2.29% (p = 0.002), left atrium (LA) diameter > 42.5 mm (p = 0.014) and LGE in the mid anterior interventricular septum (IVS) (p = 0.021), basal inferior IVS (p = 0.012) and mid inferior IVS (p = 0.012). There were no differences in LV diastolic function and LA strain between groups. Independent predictors of AF were LA diameter (p = 0.022, HR 5.933) and LGE in mid inferior IVS (p = 0.45, HR 3.280). Combining LA diameter (> 42.5 mm or < 42.5 mm) and LGE in mid inferior IVS (present or absent) in a model with four groups showed a statistically significant difference between groups (p = 0.013 for the model). Conclusions: LGE in mid inferior IVS is an independent predictor for AF occurrence in patients with HCM. Combining both LGE in mid inferior IVS and enlarged LA improves prediction of AF and may be preferred for risk stratification.